2016
DOI: 10.1038/srep20787
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic structural and optical properties of semi-polar (11–22) GaN grown on m-plane sapphire using double AlN buffer layers

Abstract: We report the anisotropic structural and optical properties of semi-polar (11–22) GaN grown on m-plane sapphire using a three-step growth method which consisted of a low temperature AlN buffer layer, followed by a high temperature AlN buffer layer and GaN growth. By introducing double AlN buffer layers, we substantially improve the crystal and optical qualities of semi-polar (11–22) GaN, and significantly reduce the density of stacking faults and dislocations. The high resolution x-ray diffraction measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…The analysis was done over a 90 • range with an interval of 30 • , where 0 • and 90 • correspond to directions [1123] and [1100], respectively. It is noted that the XRC FWHM for all samples along [1100] is broader than [1123], which are similar to the reported observations on (1122) GaN [18,[26][27][28]. For example, [1123] and [1100] planes of sample S1 shown to have the FWHM of 464 and 1390 arcsec, respectively.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The analysis was done over a 90 • range with an interval of 30 • , where 0 • and 90 • correspond to directions [1123] and [1100], respectively. It is noted that the XRC FWHM for all samples along [1100] is broader than [1123], which are similar to the reported observations on (1122) GaN [18,[26][27][28]. For example, [1123] and [1100] planes of sample S1 shown to have the FWHM of 464 and 1390 arcsec, respectively.…”
Section: Resultssupporting
confidence: 82%
“…In addition, a diffuse scattering (DS) streak parallel to [0001] direction can be seen in all samples. It has been reported that the DS steak is correlated with the presence of BSFs and PDs[18,36]. A shorter DS streak was observed in S4 compared to S1, indicating a reduction in BSFs and PDs as the flux rate decreases, which agrees with the on-axis result.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that the stripe-like and arrowhead structures were generated from asymmetric lattice mismatches of 16.1% and 1.1% between the substrate and a- GaN film along the [1–100] and [0002] directions, respectively 25 . This result could be attributed to the different probabilities for surface atom incorporation and diffusion lengths along these non-identical crystallographic directions 26 .
Figure 2 Surface structure images for samples S1, S2, S3 and S4: optical microscope images at 20 times magnification: ( a – d ), respectively; FESEM surface images: ( e – h ), respectively; and AFM images: ( i – l ), respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…As for the structural properties, HR-XRD phase analysis was utilized by majority of the research groups within the selected article, whereas XRC and RSM analyses were the least to be reported. On-and off-XRC and RSM analyses were reported to investigate defects and/or dislocations and the strain/stress, respectively [2,3,31,66,75]. It should be noted that the highest crystal qualities as investigated via XRC analysis were 300 and 325 arcsec along [23,30].…”
Section: Photoluminescencementioning
confidence: 99%